Influencia de los factores socioeconómicos en la pobreza monetaria de la región Loreto, 2022 - Shapiama Ramírez, Ivonne Raquel (2024)
Poverty is that condition in which people do not have the necessary means to satisfy basic needs, making it important to carry out research to identify and understand the causes and consequences to facilitate decisionmaking to improve the quality of life of the most vulnerable people. In this sense, the study was developed on the influence of socioeconomic factors on monetary poverty in the Loreto region, 2022. It was developed by estimating a Logit model, of a quantitative type and of a correlational level with a nonconforming design. experimental, including 1,039,372 Loretanos, as study population. The investigation determined the probability of being monetary poor increases by 4.32% if the person lives in a rural area, decreases by 7.70% as the person raises their educational level; it decreases by 11.73% if it has access to potable water; it decreases by 12.59% if you have access to electricity and increases by 5.93% as the size of the home increases. Finally, the value of Pseudo R2 = 0.2219 and Prob > chi2 = 0.000 was identified, being less than 5%, being significant, for which it is concluded that socioeconomic factors such as area of residence, education, household size, access to drinking water and electricity influence 22.19% in monetary poverty in the Loreto region, 2022.